From the secular to the post-secular. The place of religion in the local public sphere in the context of monasteries in Poland – a case study - Jewdokimow, Marcin (Revista Ciências da Religião - História e Sociedade, 2015)
The aim of the article is to reflect on the changing position of religion in the public sphere in the Polish context taking as a point of reference not attitudes or church attendance but meanings and functions of monasteries today. Monasteries in Poland are specific religion institutions because most of them had been resolved in 19th century, and only some of them were re-established in 19th and 20th century. In order to present and interpret one case (a Cistercian monastery in J?drzejów, Poland) I outline contemporary discussions on the place of religion in the public sphere referring mostly to Jurgen Habermas’ opinion shift and so called post-secular approaches. Then, I sketch characteristics of the Polish public sphere and refer shortly reasons and consequences of monasteries’ dissolution in Poland. In the final part of the text I zoom on a selected Cistercian monastery. Concluding, I do state that one may understand the monastery under scrutiny as a post-secular institution which is of a duplex nature: it is both a sacred place devoted to pastoral and contemplation functions and a source of meanings (for local identity) and cultural activities. Perceived as a historic building it is embedded in local community development plans as a tourist object. This junction characterizes its post-secular presence in the local public sphere.